Formation of Children's Character through Instilling Moral and Religious Values In Early Childhood - Esih Esih (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
The formation of a person's character is determined in the treatment at an early age. The cultivation of moral and religious values needs to be instilled early on to get a generation of character. The important thing that should get attention is the enhancement of moral and religious values in children. Qualitative description research is used in this study. To analyze the character of children obtained through observation, interviews, and communication with students, teachers, and parents. The results of the study show that children of early age (5-6 years) in Daarul Jannah Kindergarten show positive responses to the character of children in carrying out moral and religious values in the school and home environment and the future, it is expected that children have a strong personality and good characterKeywords: Early childhood, Character Building, Moral Values, Religion. AbstrakPembentukan karakter sesorang ditentukan pada perlakukan pada masa usia dini. Penanaman nilai-nilai moral dan agama perlu ditanamkan sejak dini untuk mendapatkan generasi berkarakter. Hal penting yang harus mendapatkan perhatian adalah penaman nilai moral dan agama pada anak. Penelitian diskriptik analitik kualitatif digunakan dalam studi ini. Untuk menganalisa karakter anak diperoleh melalui observasi, wawancara dan komunikasi terhadap siswa , guru dan orang tua. Hasil dari penelitian menunjukkan anak usia Dini ( 5-6 tahun) di TK Daarul Jannah menunjukan respon positif terhadap karakter anak dalam menjalankan nilai-nilai moral dan agama di lingkungan sekolah maupun rumah dan dimasa mendatang diharapkan anak memiliki kepribadian yang kokoh dan berkarakter baik.Kata Kunci : Anak Usia Dini, Pembentukan Karakter, Nilai Moral, Agama.